Job access and the labor market entry and spatial mobility trajectories of higher education graduates in the Netherlands - Marten Middeldorp (European Regional Science Association (ERSA), 2016)
The successfulness of the transition from education into working life is closely related to further career success. Graduates with good access to jobs earn higher wages and have lower chances of being unemployed. Access to jobs at the start of the career is therefore an important determinant of early career success and of importance for the whole career. In this paper, we study the effect of job access on the school-to-work transitions of recent higher education graduates. We use a GIS to calculate a job accessibility index based on driving time and use sequence analysis to calculate ideal-typical labor market entry trajectories and spatial mo-bility histories for 13,679 recent graduates of higher education. We subsequently relate job access, labor market entry trajectories and spatial mobility histories to analyze whether a suboptimal starting location in terms of job access leads to dif-fering career paths and spatial mobility trajectories. Finally, we analyze how they interact to influence early career success.
Keywords: 330; Job access; Spatial mobility; Labor market entry; Sequence analysis